The Role of Friends Againts Juvenile Delinquency Based on Social Learning Perspective - Khotimah, Kusnul; Setyawan, Katon Galih (SHAHIH: Journal of Islamicate Multidisciplinary, 2020)
The city of Blitar, also known as Patria City, was legally established on April 1stÂ , 1906. In its development, the momentum was then declared as Blitar City anniversary. In this city place lies Bung Karno, the Proclaimer, first President of Indonesia, the great ideologist and thinker of the world who is admired by boot Indonesian society and the world community. The city of Blitar is also one of the historic places for the Indonesian Nation, where prior to the proclamation of this place has been called for the independence of Indonesia followed by raising the red and white which then led to PETA rebellion by Sudanco Soeprijadi. Nevertheles, the number of juvenile delinquency jumped high in SMPN 5 Blitar ias a complex school adjacent to school SMPN 3, 5 and 6 often do deviant acts on a daily basis. The acts of deviation referred to here is an act that violates the rules or regulations in school such as smooking, ditching during class hours, and fighting on a daily basis. The method used in this research by using qualitative research approach. The results showed that Bandura, friends who stated that friend have a very big impact on oneâ€™s behaviour because one can learn everything comes from the observation of others (observational learning).